2012
DOI: 10.5194/acp-12-7015-2012
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of chemical and physical processes influencing ozone during long-range transport using a trajectory ensemble

Abstract: Abstract. During long-range transport, many distinct processes -including photochemistry, deposition, emissions and mixing -contribute to the transformation of air mass composition. Partitioning the effects of different processes can be useful when considering the sensitivity of chemical transformation to, for example, a changing environment or anthropogenic influence. However, transformation is not observed directly, since mixing ratios are measured, and models must be used to relate changes to processes. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 52 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…Also ozone is depleted rapidly in the MBL (below 1 km during this time) as a result a shift from photochemical production to destruction of ozone (as shown in Fig. 9 of (Cain et al, 2012)) associated with the higher humidity and also deposition of species to the ocean surface such as nitric acid and ozone itself .…”
Section: Tracers In the Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Also ozone is depleted rapidly in the MBL (below 1 km during this time) as a result a shift from photochemical production to destruction of ozone (as shown in Fig. 9 of (Cain et al, 2012)) associated with the higher humidity and also deposition of species to the ocean surface such as nitric acid and ozone itself .…”
Section: Tracers In the Modelmentioning
confidence: 99%
“…However, there were marked episodes of cross-coastal pollutant transport, some of which were observed by research aircraft as the air crossed the Atlantic to the Azores and Europe (Methven et al, 2006;Owen et al, 2006). Chemical processing following air masses for several days during these ICARTT Lagrangian cases has been examined in detail by Real et al (2008); Lee et al (2011);Cain et al (2012); Davis et al (2012).…”
Section: L Peake Et Al: Coastal Outflowmentioning
confidence: 99%
See 2 more Smart Citations
“…Methven et al [21] advanced a novel Lagrangian method of tracking observed plumes across the North Atlantic (including the 7/20 case study) through the use of whole air samples from the aircraft intercepts to construct hydrocarbon footprints in conjunction with trajectory model forecasts. Real et al [22] and Cain et al [23] added to this Lagrangian approach, advancing new insights into the processes influencing the plume's chemical transformation and ozone production in particular based upon photochemical model simulations. In addition, these authors advanced that potential errors in their Lagrangian analyses may have derived from uncertainties in the lower tropospheric wind fields used to force the trajectory forecasts and diagnose mixing and transport in their simulations.…”
Section: Introductionmentioning
confidence: 99%